Development of an Environment-Friendly and Solvent-Free Synthetic Route for the Synthesis of 3,4-Dihydropyrimidin-2-(1H)-Ones/Thiones Using La(NO3)3.6H2O as an Efficient Catalyst - Mohamadpour, Farzaneh (UI Scholars Hub, 2018)
We present a facile and environmentally friendly procedure for the synthesis of corresponding 3,4-dihydropyrimidin-2-(1H)-ones/thiones derivatives. The synthesis was achieved using aone-pot three-component Biginelli reaction among β-keto esters (methyl or ethyl acetoacetate), aromatic aldehyde (benzaldehyde derivatives), and urea or thiourea in the presence of lanthanum (III) nitrate hexahydrate (La(NO3)3.6H2O), as a highly efficient catalyst under solvent-free conditions. This protocol has numerous advantages: it isan inexpensive, non-toxic, simple reaction work-upcatalyst with a high atom-economy, and shows excellent yields with short reaction times.